Comparative bacteriology of chronic blepharitis. - Dougherty, J M (1984)
One hundred and fifteen patients with chronic blepharitis were compared with 47 normal controls. Six clinically distinct groups of blepharitis were observed: staphylococcal; seborrhoeic, alone, with associated staphylococcal superinfection, meibomian seborrhoea, or secondary inflammation of the meibomian glands; and meibomian keratoconjunctivitis (MKC). Staphylococcus aureus was isolated in appreciable frequency from the staphylococcal and the mixed staphylococcal/seborrhoeic groups in contrast to the normal and non-staphylococcal groups. Coagulase-negative Staphylococcus spp., Propionibacterium acnes, and cornyneform bacteria were the most commonly isolated bacteria from the lid for all groups. Cultures of material expressed from the meibomian glands yielded similar organisms but in reduced frequency. Testing of antibiotic susceptibility revealed Staph aureus to be usually sensitive to most commonly used ophthalmic antimicrobials except sulphonamides.